2001
DOI: 10.1108/07363760110392967
|View full text |Cite
|
Sign up to set email alerts
|

Spot the difference: consumer responses towards counterfeits

Abstract: Examines consumers’ motivation for buying counterfeits or pirated goods. The findings indicated that, compared to those who did not buy pirated music CDs, those who bought the counterfeits viewed such purchases as less risky, and trusted stores that sell counterfeits more. They did not see counterfeits as too unfair to singers or the music industry, thought they benefit the society more, and did not see people who buy them as unethical. We also investigated the influence of social, personality, and demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 378 publications
(130 citation statements)
references
References 12 publications
2
71
1
1
Order By: Relevance
“…Low-income consumers are relatively less sensitive to ethical issues involved in a purchase decision than high-income consumers (Ang et al 2001;Muncy, Vitell 1992). In Asian countries both buyers and non-buyers of counterfeits irrespective of their income levels consider purchasing of counterfeits a normal buying behavior (Ang et al 2001). Similar situation prevails in the West particularly in USA (Norum, Cuno 2011).…”
Section: Ethical Sensitivitymentioning
confidence: 75%
See 3 more Smart Citations
“…Low-income consumers are relatively less sensitive to ethical issues involved in a purchase decision than high-income consumers (Ang et al 2001;Muncy, Vitell 1992). In Asian countries both buyers and non-buyers of counterfeits irrespective of their income levels consider purchasing of counterfeits a normal buying behavior (Ang et al 2001). Similar situation prevails in the West particularly in USA (Norum, Cuno 2011).…”
Section: Ethical Sensitivitymentioning
confidence: 75%
“…Positive WOM about the counterfeits inspires more consumers to buy them. Ang et al (2001) suggested that genuine industry should use WOM communication to discourage the purchasing of counterfeits. Muncy, Vitell's (1992) findings that low-income consumers are ethically insensitive in buying situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, research has shown that the willingness of consumers to purchase counterfeit products is negatively related to their attitudes toward lawfulness [11]. Consumers with lower ethical standards are expected to experience less guilt when purchasing a counterfeit product [20]. Instead, such consumers rationalize their behavior in order to reduce the cognitive dissonance of an unethical behavior.…”
Section: Integritymentioning
confidence: 99%